Indigenous Healers' beliefs and practices concerning sexually transmitted diseases - FM Mulaudzi; ON Makhubela-Nkondo (AOSIS, 2006)
A Grounded Theory study has been used, based on its Theory of Symbolic Interactionism, to explore indigenous healers' beliefs and practices concerning sexually transmitted diseases amongst the Vhavenda. Initial data collection has been done, using purposive sampling and when categories started emerging, theoretical sampling was then used. Data were analysed by using three basic types of coding namely, open coding, axial coding and selective coding. The findings of the study revealed a variety of terms used to identify STDs. It then also became evident that there are similarities between gonorrhoea, syphilis and condylomata as shown in the orthodox Sexually transmitted diseases posters used in orthodox medicine with some of the STDs that the indigenous healers are familiar with. In accordance with the Grounded Theory, the description of types of diseases, disease patterns as well as signs and symptoms culminated in the emergence of the Dirt Theory. Based on the above findings, it was recommended that guidelines for designing a module for teaching health professionals be formulated to assist nurses in understanding the beliefs and practices of the people they serve.